Mesolithic and Neolithic material productions in Aveyron (France) during the 6th millennium BC: Originality or adaptability?. (10th April 2018) - Defranould, Elsa; Caro, Joséphine; Bobœuf, Marc; Manen, Claire; Perrin, Thomas
Abstract: During the 6th millennium BC, southern France was affected by deep cultural changes in the form of the western Mediterranean Neolithization process; a turning point in subsistence agriculture and husbandry. In southern France, the department of Aveyron has several archeological sites attributed to a particular Early Neolithic culture, historically named « Roucadourien », which was previously interpreted as the result of an autonomous Neolithization or as the process of indigenous acculturation. Today, the reliability of these archaeological contexts and the definition of this vast and homogenous cultural entity are being questioned. Revisions of this regional data take place within the European Neolithization debate and allowed us to discuss and test the main hypotheses: demic or cultural diffusion. The aim of this research was to consider this Continental entity using new paradigms, and not only in terms of central, peripheral or marginal territory within the Neolithization process. In order to shed new light on this debate, it was important to review all the material data provided by these sites. Recent typo-technological studies on the lithic and ceramic assemblages from some sites of the Aveyron department (Combe-Grèze, Clos de Poujol, Roquemissou and Les Usclades) allowed us to renew our perception of these south-western contexts, and made it possible to assess the analysis of these sites from both a cultural and a functional point of view. Therefore, this study should be considered as a step towards a deeper understanding of cultural relationships and technical know-how transfers between the Second Mesolithic and the Early Neolithic. This revision highlights stratigraphical mixtures, evidence of functional variability and/or cultural recombining derived from the coastline area.